PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMISARIS INDEPENDEN, KONSENTRASI KEPEMILIKAN, LEVERAGE DAN PROFITABILITAS TERHADAP INTELLECTUAL CAPITAL DISCLOSURE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Julia Elfika Lutfiana, 13.05.52.0181; Aini, Nur (Students Journal of Accounting and Banking, 2017)
The study examines the effect of companyâs size, companyâs age, independent commissioner, ownership concentration, leverage and profitability influence simultaneously on the intellectual capital disclosure. The population of this research is all manufacturing companies listed on Indonesia Stock Exchange for year of 2013 to 2015. The study employs purposive sampling resulted 215 sample. Method of data analysis of the study is multiple regression analysis. The study found that companyâs age, independent commissioner, ownership concentration and leverage do not affect the intellectual capital disclosure. Moreover companyâs size and profitability indluence intellectual capital disclosure.Keywords: Intellectual Capital Disclosure, Companyâs Size, Companyâs Age, Independent Commissioner, Ownership Concentration, Leverage and Profitability